C- and S-rich molten alloy immiscibility and core formation of planetesimals - Corgne, A; Wood, B; Fei, Y (2008)
We present the results of melting experiments to 7.7 GPa and 2200 °C on a synthetic 'chondrite-like' composition suitable to model early planetesimal differentiation. Our principal observation is that two immiscible liquid alloys coexist to about 5.5 GPa in Fe-Ni-S-C-O compositional space, with one liquid alloy being enriched in S and the other enriched in C. The chemical distinctions between the two liquid alloys progressively weaken as pressure increases. This is related to the contraction of the miscibility gap with increasing pressure. With the moderately C- and S-depleted composition used in this study, we observed closure of the miscibility gap at about 5.5 GPa. Our results have implications for core formation on planetary bodies that have undergone extensive melting. Because of the characteristics of the immiscibility region, core formation and differentiation histories would have been largely dependent on the size of these bodies and their C and S contents. Our results indicate that relatively small bodies with elevated S and C contents would have likely experienced significant core stratification. © 2008 Elsevier Ltd. All rights reserved.